Evaluation, Standardized Tests and Training Processes: Experiences in Secondary Schools in North of Mexico - Arzola-Franco, David Manuel (2017)
In this research, an analysis of policies and implementation processes of testinghigh school students in the State of Chihuahua, Mexico is presented. The objectiveis aimed at understanding how these practices guide or outline the dynamics ofschools, teachers and priorities of student work. The information was collectedthrough interviews, focus groups and observation records. The results indicatethat the approach that has made the assessment reinforces a school culture thatfavors the numerical results over the educational processes, competitivenessand individual success is exalted above solidarity and empathy. The evaluationapproach embodied in the curriculum and assessment practices in classrooms iscontradicted.